2008
DOI: 10.1038/bjp.2008.175
|View full text |Cite
|
Sign up to set email alerts
|

The μ‐opioid receptor agonist morphine, but not agonists at δ‐ or κ‐opioid receptors, induces peripheral antinociception mediated by cannabinoid receptors

Abstract: Background and purpose: Although participation of opioids in antinociception induced by cannabinoids has been documented, there is little information regarding the participation of cannabinoids in the antinociceptive mechanisms of opioids. The aim of the present study was to determine whether endocannabinoids could be involved in peripheral antinociception induced by activation of m-, d-and k-opioid receptors. Experimental approach: Nociceptive thresholds to mechanical stimulation of rat paws treated with intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 52 publications
2
47
0
1
Order By: Relevance
“…Recent evidence suggests a role of MCP-1/CCL2 in opioid tolerance (Zhao et al, 2012). Given that m-opioid and cannabinoid receptors are widely expressed in both the CNS and periphery, it is important to note that the observed behavioral effects may be due to receptor function at the peripheral nociceptors (Desroches et al, 2014), dorsal root ganglia (Khasabova et al, 2004), dorsal horn of the spinal cord (da Fonseca Pacheco et al, 2008;Desroches et al, 2014), and periaqueductal gray and other brain regions (Páldy et al, 2008;Wilson-Poe et al, 2015) implicated in the regulation of nociception. CB 1 and CB 2 receptors appeared to play a differential role in mediating the antinociceptive effects of morphine and MJN110 given in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests a role of MCP-1/CCL2 in opioid tolerance (Zhao et al, 2012). Given that m-opioid and cannabinoid receptors are widely expressed in both the CNS and periphery, it is important to note that the observed behavioral effects may be due to receptor function at the peripheral nociceptors (Desroches et al, 2014), dorsal root ganglia (Khasabova et al, 2004), dorsal horn of the spinal cord (da Fonseca Pacheco et al, 2008;Desroches et al, 2014), and periaqueductal gray and other brain regions (Páldy et al, 2008;Wilson-Poe et al, 2015) implicated in the regulation of nociception. CB 1 and CB 2 receptors appeared to play a differential role in mediating the antinociceptive effects of morphine and MJN110 given in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid amide hydrolase associations with opioid outcomes Research Article vice versa [40]. In fact, CB agonists enhance the effect of μ-opioid receptor agonists in a variety of models of analgesia [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined interactions between the cannabinoid and opioid systems by administering CB1 agonists in combination with morphine and have consistently shown that CB1 agonists enhance the antinociceptive effects of morphine (Smith and Martin, 1992;Welch and Stevens, 1992;Smith et al, 1994;Welch et al, 1995;Massi et al, 2001). More recent studies using CB1 antagonists also provide evidence that endogenous cannabinoids mediate the antinociceptive effects of morphine (da Fonseca Pacheco et al, 2008;Pacheco et al, 2009;Miller et al, 2011). Moreover, morphine's antinociceptive effects are enhanced when AEA is protected from metabolism (da Fonseca Pacheco et al, 2008;Haller et al, 2008;Pacheco et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CB1 antagonists attenuate morphine-induced antinociception in the hotplate, writhing, and tail-flick tests (Pacheco et al, 2009;Miller et al, 2011) and in models of hyperalgesia (da Fonseca Pacheco et al, 2008). Exogenously administered AEA in combination with the FAAH inhibitor cyclohexylcarbamic acid 3Ј-carbamoylbiphenyl-3-yl ester (URB597), N-(4-hydroxyphenyl)arachidonylamide (AM404) enhances the antinociceptive effects of morphine in the tail-flick test (Haller et al, 2008), and methylarachidonoylflurophosphate, which inhibits the degradation of the endogenous cannabinoids AEA and 2-arachidonoylethanolamine, enhances the antinociceptive effects of morphine in the tail-flick test and in hyperalgesia models (da Fonseca Pacheco et al, 2008;Pacheco et al, 2009).…”
Section: Introductionmentioning
confidence: 99%